Change of the Optoelectronic Properties of Semiconductor Compounds Induced by Nanosecond Laser Irradiation Pulses - Levytskyi, S.; Cao, Z.; Koba О.; Koba М. (Physics and Chemistry of Solid State, 2024)
New research has discovered discrepancies in the melting points, plasma generation, and resulting changes in optoelectronic properties of semiconductor materials A2B6 and A3B5 when exposed to laser light, even when the experimental conditions are the same. Therefore, accurately determining the thresholds at which these complex semiconductor compounds melt and create plasma remains an unsolved task. This work utilizes nanosecond ruby laser irradiation to thoroughly examine fundamental characteristics of semiconductor compounds A2B6 and A3B5 when exposed to laser irradiation. This includes investigating the thresholds at which melting occurs, the production of plasma, and any changes in optoelectronic capabilities. The experimental results demonstrate notable discrepancies in the melting points and optoelectronic characteristics of various semiconductor materials when subjected to the same experimental conditions. The variations mostly arise from inherent statistical biases in the parameters of the sample. By employing photoacoustic and photoconductive techniques, we accurately ascertained the melting points of cadmium telluride, gallium arsenide, and aluminum gallium arsenide crystals, providing exact empirical data on the characteristics of these corresponding substances. In addition, we performed photoconductive spectroscopy tests on cadmium telluride exposed to nanosecond ruby laser pulses. We noticed a significant impact of the creation of a tellurium layer on the photoconductivity. The investigations showed that the existence of a tellurium layer results in photoconductivity that varies depending on the spectrum, with the most significant improvement observed in the short-wavelength region.